2020
DOI: 10.1128/aem.00596-20
|View full text |Cite
|
Sign up to set email alerts
|

Legacy of a Butterfly’s Parental Microbiome in Offspring Performance

Abstract: An insect’s phenotype can be influenced by the experiences of the parental generation. However, the effects of the parental symbiotic microbiome and host plant use on the offspring are unclear. We addressed this gap of knowledge by studying Pieris brassicae, a multivoltine butterfly species feeding on different brassicaceous plants across generations. We investigated how disturbance of the parental bacterial community by antibiotic treatment affects F1 larval traits. We tested the effects depending on whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 78 publications
0
9
1
Order By: Relevance
“…[ 18 , 34 , 39 41 ]. In contrast to other studies that found very low bacterial abundances in P. brassicae caterpillars [ 42 ], estimation of the bacterial abundance by qPCR suggested higher bacterial densities in our samples. This was confirmed by plating a selection of samples on trypticase soy agar supplemented with 0.5 g/L cycloheximide (up to10 4 bacterial colony forming units (cfu) per specimen) (Additional file 1 : Table S9).…”
Section: Discussioncontrasting
confidence: 99%
“…[ 18 , 34 , 39 41 ]. In contrast to other studies that found very low bacterial abundances in P. brassicae caterpillars [ 42 ], estimation of the bacterial abundance by qPCR suggested higher bacterial densities in our samples. This was confirmed by plating a selection of samples on trypticase soy agar supplemented with 0.5 g/L cycloheximide (up to10 4 bacterial colony forming units (cfu) per specimen) (Additional file 1 : Table S9).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that changes in relative abundances of genera for the three populations were related to ETEC-positive (Kruskal–Wallis p -value < 9 × 10 −4 ), EAEC-negative ( p -value < 0.0058), and Giardia -positive ( p -value < 0) individuals. Later, we combined the microbiome OTU genera data with all demographic (gender, age, location) and clinical data (BMI, symptoms, presence of pathogens and parasites) to assess the association of the microbiome data with these factors through generalized mixed models [ 48 ]. For simplicity, in these tests we utilized only the differentially abundant genera: Sutterella , Faecalibacterium , Clostridium , Prevotella , Parabacteroides , Butyrivibrio , Dialister , and Odoribacter , and the demographic and clinical data as response variables.…”
Section: Resultsmentioning
confidence: 99%
“…To date, evidence of transgenerational effects of the microbiota in insects is in general scarce, this is especially true for Lepidoptera. The impact of parental microbiota on the fitness of their offspring was recently tested in the large cabbage white butterfly, Pieris brassicae (Paniagua Voirol, Weinhold, Johnston, Fatouros, & Hilker, 2020). This study showed that altered microbial community in the mothers has no detrimental effects on the performances of their offspring when both parents and larvae fed the same host plant, but it negatively affects offspring feeding on host plants with higher sinigrin (a defensive metabolite) content than the host plant on which the mothers fed (Paniagua Voirol et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of parental microbiota on the fitness of their offspring was recently tested in the large cabbage white butterfly, Pieris brassicae (Paniagua Voirol, Weinhold, Johnston, Fatouros, & Hilker, 2020). This study showed that altered microbial community in the mothers has no detrimental effects on the performances of their offspring when both parents and larvae fed the same host plant, but it negatively affects offspring feeding on host plants with higher sinigrin (a defensive metabolite) content than the host plant on which the mothers fed (Paniagua Voirol et al, 2020). The authors suggest that disturbances in the parental microbiota may affect the ability of their offspring to cope with the stress of host plant shift.…”
Section: Discussionmentioning
confidence: 99%